A novel energy harvesting approach for hybrid electromagnetic-based suspension system of off-road vehicles considering terrain deformability. (1st January 2021) - Taghavifar, Hamid
Highlights: The problem of energy harvesting from off-road vehicles is addressed using a hybrid electromagnetic-based suspension system. The deformable terrain stiffness effect on harvestable power is explored based on Terramechanics theories. The electromagnetic suspension energy harvester dynamics of circuitry is incorporated. Abstract: Hydraulic shock absorbers are the exclusive components to attenuate the transmitted vibration to the chassis and also to improve the ride quality accordingly. Simultaneously, the shock absorbers contribute to the enhancement of the handling dynamics during cornering maneuvers through constrained roll mode of motion. Energy recovery using shock absorbers is essential for energy management/energy efficiency in the automotive industry. The main contributions of the present paper concerned with the energy harvesting from off-road vehicles are i) considering a hybrid electromagnetic based suspension system running independent from any on–off control strategy, ii) incorporating the dynamics of the electromagnetic energy harvester circuitry to shed light on the practical aspects of energy recovery, and iii) including the deformable terrain stiffness variations based on Terramechanics theories. Additionally, the effect of harvestable power on the ride comfort of the driver/passenger is investigated based on a filtered acceleration response of the chassis in both the frequency and time domains. A Monte Carlo sensitivity analysis is also employed to explore the effect of different variable randomness on the maximum exploitable energy from the suspension system. Obtained results revealed that a maximum of about 48 W power can be recovered from the hybrid suspension system under the nominal suspension parameters at about 54 km/h of forward speed on a deformable clay-loam soil. Additionally, it was inferred that the most substantial impact on the harvestable energy is attributed to the electromagnetic energy harvester coil internal resistance, the front suspension damping coefficient, the harvester circuitry external load resistance and the soil-tire equivalent stiffness value, respectively.